Treinamento com restrição de fluxo sanguíneo e o efeito crônico no processo do destreinamento da força muscular - Pinto, Edna Ferreira (2023)
Introduction: The effects of treatment can be observed from four weeks after the cessation of physical exercises, although muscle strength is presented differently among the physical components involved in the research. The central question of this thesis is whether or not strength training performed with the technique of blood flow restriction is effective in delaying the effect of muscle strength detainment? The experimental hypothesis is that muscle strength training using the blood flow restriction technique reduces the decrease in strength caused by distraining. Objective: to analyze the chronic effect of blood flow restriction training on the process of muscle strength detainment. Materials and Methods: quantitative, experimental and longitudinal research, with a sample of men and women between 20 and 40 years of age (N=15). The exercises were carried out with bar, being development shoulder, direct rope, crocheting and extension chair, having the dynamic muscular strength as a dependent variable. The subjects were randomized and randomized into three groups, with training with RFS being trained with 20% of 1RM (N=5) group consisting of three men and two women; training with bodybuilding (N =7), containing three men and four women in the group, 60% of 1RM; and training with preconditioned ischemia (220 mmHg) of occluded flow(N=3), group consisting of two men and a woman. The duration of eight weeks of training and twelve entraining, three times a week and on alternating days. The normality of the data was verified by the Shapiro-Wilk test; and the Variance Analysis (Anova one way) pre- and post-intervention during de-treatment. The adopted significance level was p≤0,05. Results: indicate that the dynamic muscle strength gained for longer, for the RFS group in the development exercise (p=0.001) and the size of the effect (η2=0.11) in the extender chair (p = 0.044) and, effectively (η 2=0.61). Conclusion: The study concluded that the RFS technique was more efficient for treatment compared to other training methods, such as bodybuilding and pre-conditioning ischemia.